Clinicodemographic profile of VKC patients in tertiary care centre of North India: A prospective study - Manpreet Kaur; Malvika Sharma; Nancy Sharma (TNOA Journal of Ophthalmic Science and Research)
Objective: To know the demography and clinical profile of patients of vernal keratoconjunctivitis (VKC) in a tertiary care center over a period of 6 months from April 2023 to September 2023. Methods: A prospective, hospital-based study including a total of 250 patients with Vernal Keratoconjunctivitis (VKC) studied from April 2023 to September 2023 in a tertiary care center in north India. This study had a diagnosis of vernal keratoconjunctivitis (VKC) on the basis of their history, symptoms, and clinical findings. Detailed history was taken from each patient including age at the onset of the disease, gender of the patient, any seasonal variations, his/her place of residence, and any associated allergic or “atopic” illnesses. A thorough examination was done to find out visual acuity, condition of the cornea, limbus, bulbar, palpebral conjunctiva, and associated complications. Results: Out of 250 patients, VKC was more common in male (84.4%) than female (15.6%) patients with maximum cases seen between 6 and 10 years of age. The majority of cases were reported in summer in the month of May and June. The palpebral form was predominant among all that is around 180 (72%) cases, followed by mixed 54 (21.6%) and Limbal form 16 (6.4%). The most common symptom was itching (100%) seen in almost all cases. Palpebral papillae were the commonest signs. Associated allergic conditions were found in 17 (6.8%) patients. Conclusion: This study represents the nature of Vernal Keratoconjunctivitis and its presentation in North India, showing regional variations in the presentation of the disease due to different environmental conditions and the variations in aggression in management protocol. It also emphasizes the regular monitoring of intraocular pressure and the supervision of rising Adult onset VKC.